Dietary caprylic acid and ghrelin O-acyltransferase activity to modulate octanoylated ghrelin functions: What is new in this nutritional field?. (August 2018) - Lemarié, Fanny; Beauchamp, Erwan; Drouin, Gaëtan; Legrand, Philippe; Rioux, Vincent
Highlights: Caprylic acid belongs to the class of medium-chain saturated fatty acids (MCFAs). Caprylic acid was shown to acylate ghrelin, the only known peptide hormone with an orexigenic effect. Dietary caprylic acid is suspected to provide the ghrelin O-acyltransferase (GOAT) enzyme with octanoyl-CoA co-substrates. Both dietary caprylic acid availability and GOAT activity may be important to modulate octanoylated ghrelin concentration and functions. This review summarizes studies that have investigated how diet may affect ghrelin octanoylation. Abstract: Caprylic acid (octanoic acid, C8:0) belongs to the class of medium-chain saturated fatty acids (MCFAs). Dairy products and specific oils such as coconut oil are natural sources of dietary caprylic acid. MCFAs display distinct chemico-physical and metabolic properties from those of long-chain saturated fatty acids (LCFAs ≥ 12 carbons) and potential beneficial physiological effects of dietary C8:0 have been studied for many years. More recently, caprylic acid was shown to octanoylate ghrelin, the only known peptide hormone with an orexigenic effect. Through its covalent binding to the ghrelin peptide, caprylic acid exhibits an emerging and specific role in modulating physiological functions themselves regulated by octanoylated ghrelin. Dietary caprylic acid is therefore now suspected to provide the ghrelin O-acyltransferase (GOAT) enzyme with octanoyl-CoA co-substrates necessary for the acyl modification of ghrelin. Recent studies suggest that decreasing the circulating octanoylated ghrelin level through the inhibition of GOAT activity, or simply by modulating the availability of its C8:0 substrate, might constitute a therapeutic strategy against obesity. Both dietary caprylic acid availability and GOAT activity may indeed be important to modulate octanoylated ghrelin concentration and functions. This review highlights recent findings in the field of nutrition.